Properties of a sympatho-inhibitory and vasodilator reflex evoked by superior laryngeal nerve afferents in the cat. - Bachoo, M (1985)
The background discharge of sympathetic preganglionic neurones shows a marked inspiration-synchronous component which is known to originate from within the central nervous system. The contribution of this component to total neurogenic vasoconstrictor tone is unknown. In order to estimate its extent we have exploited the inspiration-suppressing effect of a group of low threshold afferent fibres in the superior laryngeal nerve. The electrical activities of the cervical sympathetic trunk and of the phrenic nerve were recorded in pentobarbitone-anaesthetized, paralysed, artificially ventilated, sino-aortic denervated and vagotomized cats, together with the perfusion pressure of an innervated hind limb perfused at a constant flow rate. Repetitive stimulation of the superior laryngeal nerve at an intensity just sufficient to suppress phrenic nerve activity inhibited the inspiration-synchronous sympathetic discharge and caused hind limb vasodilatation. This vasodilatation was abolished by hexamethonium or phentolamine, but was not affected by atropine or propranolol. Following the elimination of phrenic nerve activity and inspiration-synchronous sympathetic discharge by systemic hypocapnia, repetitive stimulation of the superior laryngeal nerve either failed to affect the residual sympathetic activity and hind limb perfusion pressure, or caused an increase of both. Stimulation of the superior laryngeal nerve with short (0.2 s) trains of stimuli, delivered at selected times of the respiratory cycle for several consecutive cycles, had similar effects on phrenic nerve bursts, inspiration-synchronous sympathetic discharge and hind limb perfusion pressure. Stimulation at progressively earlier times during inspiration produced a graded reduction in all three variables, while stimulation during late inspiration or early expiration had no effect on any of them. The results suggest that the vasodilator reflex, elicited by inspiration-suppressing afferents in the superior laryngeal nerve, results from selective abolition of the excitatory input which causes the inspiration-synchronous discharge of sympathetic neurones. The magnitude of the hind limb vasodilatation can therefore be taken as an indication of the extent of control of hind limb vasoconstrictor tone exerted by this particular input. By comparing the magnitude of the reflexly evoked vasodilatation with that of the vasodilatation resulting from ganglionic blockade, it was estimated that 24.2% of the neurogenic vasoconstrictor tone of the hind limb was attributable to the inspiration-synchronous component of sympathetic discharge.